Modelling And Simulation Of Retentate-Permeate Recycle Premeator For The Enrichment Of Methane - Choong, Thomas S. Y.; Abd. Aziz, Ramlan (Penerbit UTM Press, 2002)
The purity of less permeable component (CH4) can be enhanced by using a retentatepermeate recycle permeator. A mathematical model has been derived and the effect of some parameters on the retentate purity and recovery have been studied through simulation. The retentatepermeate recycle permeator has been found to be more effective at low pressure ratio, low composition of the less permeable component in the feed, and large ideal selectivity. There is an optimal range of dimensionless membrane area for effective recycle. The applicability of retentate-permeate recycle permeator in enrichment of methane from biogas and natural gas has been considered. It was found that the retentate-permeate recycle permeator has the potential to be used in enrichment of methane in biogas.